THE CORRELATION BETWEEN STUDENTS’ VOCABULARY AND THEIR TRANSLATION ABILITY AT SMK NAHDLATUL ULAMA - Eska Perdana Prasetya; Jalaluddin Baharsyah (STKIP PGRI Jombang, 2020)
ABSTRACTThis research is aimed to answer whether or not there is a significant correlation between students’ vocabulary mastery and their translation ability. In this research, the researcher used a correlational method in a quantitative design. The data were collected through a vocabulary test and a translation test. The finding showed that the students’ vocabulary mastery is fair, it is showed by the mean score of the test that is 61.3. The students’ translation ability is fair also the mean score of the test that is 60.6. The regression model is significant with F-observed 118.41which was less than the F table 7.64 in 1% level of error. The correlation between students’ vocabulary mastery and their translation ability is linear with F-observed 1.97 which less than F table 3.52 in 1% level of error. There is a positive correlation between the two variables whose total 0.902 (very high correlation). The coefficient determination is 81%, it means that translation ability 81% was affected by the students’ vocabulary mastery and the rest was 19% was affected by the other variables or factors.